IMPLEMENTATION OF THE TWO STAY TWO STRAY MODEL TO INCREASE SOCIAL STUDIES LEARNING OUTCOMES - Kustanto Kustanto (Kopertis Region IV Jabar and Banten, 2023)
This study examines how effective the application of the Two stay Two Stray model is in increasing social studies learning outcomes in grade IV public elementary school 2 Pungan. This research uses a type of classroom action research where two cycles will be carried out, each cycle consisting of two meetings. The subjects in this study were all 14 students of class IV. Sources of data in the study were obtained from the learning outcomes of 14 students, there were 9 students who had not yet mastered the teaching criteria and 5 students had achieved mastery. Data collection techniques were obtained from the results of observations at each meeting and the administration of written tests. The research procedure consists of problem identification, problem analysis, preparation of action plans, implementation of observations, and preparation of a final report. This research will be carried out in two cycles. In each cycle, two meetings are held which describe the action, action planning, implementation of observation, analysis and reflection at the end of each meeting. Based on data on social studies learning outcomes, class IV students have experienced an average increase starting from before being given treatment (pre-action), cycle I, and cycle 2. The average score before being given treatment using the two stay two stray learning model is 59.3, after given learning improvement treatment in cycle 1 the average was 71.3 and 87.7 in cycle 2 with KKM 70.